Avocado Consumption Increased Skin Elasticity and Firmness in Women ‐ A Pilot Study. (17th January 2022) - Henning, Susanne M.; Guzman, Jeraldine B.; Thames, Gail; Yang, Jieping; Tseng, Chi‐Hong; Heber, David; Kim, Jenny; Li, Zhaoping
Abstract: Background: Avocados are a rich dietary source of monounsaturated fatty acids, carotenoids, and phenolic compounds. Clinical studies have demonstrated that oral consumption of carotenoids improved skin aging. However, no studies have investigated whether oral intake of avocado will reduce skin aging. Objectives: We therefore performed this pilot study to assess whether oral consumption of one avocado daily for 8 weeks can reduce skin aging in healthy overweight women assessing skin physical characteristics and resistance to UVB radiation. Methods: Thirty‐nine female participants (age 27–73 years) with Fitzpatrick skin type II‐IV were randomly assigned to consume either one avocado daily or continue habitual diet for 8 weeks. Facial skin elasticity, firmness, pigmentation, sebum, and hydration were determined using a cutometer on the forehead and under eye. Minimal erythema dose (MED) was determined by standardized protocol at inner arm. Results: Elasticity and firmness were increased at forehead comparing 8 weeks to baseline in the avocado group. Comparing avocado to control, change in firmness marker from baseline to week 8 indicated a significant increase in forehead skin firmness in the avocado group. We did not observe any change in hydration, pigmentation, sebum, and UVB resistance between the avocado and control group, although changes in melanin and erythema were observed in both groups over time. Conclusions: Our findings suggest that daily oral avocado consumption may lead to enhanced elasticity and firmness of the facial skin in healthy women. Further studies of other skin locations are required to establish the connection between avocado consumption and skin aging.